Dr. Asaad Houmd and his Approach to the Causes of Revelation in his Interpretation of the Easiest Interpretations (Islamic Sciences Journal, 2023)
The reason for the revelation is a story that the Qur’an derives from the reality presented by the Holy Qur’an based on stories that occurred in the time of the Prophet Muhammad, may Allah bless him and grant him peace, or a question people asked of the Holy Prophet. According to the reader and the listener, it is a preparation for the reader and an incentive for the Noble Qur’anic text. That is why we find many interpreters issuing it and presenting it in their interpretations, to make it the first thing mentioned in Their study of the Qur’anic texts, as they mention them on the occasion of the revelation of this Qur’anic text to what came before it and what comes after it. This science is considered a completely independent science, with its theories and codified applications, knowing that it is not cut off from the other sciences, rather all of these sciences are integrated into one destination except. It is the service of the Book of Allah Almighty, the Noble Qur’an, and for the reason of the revelation there are many benefits that the reader cannot dispense with in any case, as I touched on all these points in this research in detail and in detail.